2006
DOI: 10.1103/physrevlett.96.167003
|View full text |Cite
|
Sign up to set email alerts
|

Large Anisotropic Normal-State Magnetoresistance in CleanMgB2Thin Films

Abstract: We report a large normal-state magnetoresistance with temperature-dependent anisotropy in very clean epitaxial MgB2 thin films (residual resistivity much smaller than 1 microOmega cm) grown by hybrid physical-chemical vapor deposition. The magnetoresistance shows a complex dependence on the orientation of the applied magnetic field, with a large magnetoresistance (Delta(rho)/(rho)0=136%) observed for the field H perpendicular ab plane. The angular dependence changes dramatically as the temperature is increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 25 publications
5
51
0
Order By: Relevance
“…For a multi-band superconductor, the transport behaviour at different bands may be affected by magnetic field individually and thus the MR is more commonly observed. The MgB 2 superconductor is a very good example, in which MR as large as 136% (at 45 K, 18 T) has been observed [30]. However, for a less clean sample, the scattering is strong and MR could be suppressed considerably.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For a multi-band superconductor, the transport behaviour at different bands may be affected by magnetic field individually and thus the MR is more commonly observed. The MgB 2 superconductor is a very good example, in which MR as large as 136% (at 45 K, 18 T) has been observed [30]. However, for a less clean sample, the scattering is strong and MR could be suppressed considerably.…”
Section: Resultsmentioning
confidence: 96%
“…As for FeSe and other iron-based superconductors, it has also been confirmed that multiple bands contribute to the transport properties [29]. We try to fit the MR using a two-band model [30] which gives the relation…”
Section: Resultsmentioning
confidence: 97%
“…It is known that the magnetoresistance (MR) is a very powerful tool to investigate the electronic scattering and the message of the Fermi surface. For example, in MgB 2 , a large magnetoresistance was found which is closely related to the multiband property 21,22 . Fig.…”
Section: Resultsmentioning
confidence: 98%
“…According to the Kohler's law 25 , MR at different temperatures can be scaled by the expression ∆ρ/ρ 0 = f (Hτ ) = F (H/ρ 0 ) with the assumption that scattering rate 1/τ (T ) ∝ ρ 0 (T ), here f and F represent some unknown functions. For MgB 2 , the Kohler's law is not obeyed because of the multiband property 21 . Here we tried the scaling based on the Kohler's law to the data from the single crystal (SC sample II), the result is shown in the inset of Fig.2(a).…”
Section: Resultsmentioning
confidence: 99%
“…Larger film thickness results in higher T c , lower ρ 0 , and higher RRR [44]. Li et al reported a large anisotropic normal-state magnetoresistance (∆ρ/ρ 0 =136% for the H ┴ ab plane at 18T) in clean MgB 2 thin films [45]. This is a direct result of the multiband nature of MgB 2 and the cleanness of the HPCVD films.…”
Section: Single-crystal Like Mgb 2 Thin Filmsmentioning
confidence: 89%